SYTUACJA PRAWNA DYSPONENTA KNOW-HOW - Bielecka-Dobroczek, Aleksandra (Zeszyty Prawnicze, 2017)
LEGAL POSITION OF KNOW-HOW HOLDER Summary The subject of the article is the reconstruction of the meaning of the term know-how and the analysis of its holder’s legal position. Know-how is defined as technical, commercial, financial knowledge or experiences of any other kind, which are useful in trade or learned professions. The legal goods that are patented or registered cannot be considered as know-how. The knowledge consisting in know-how must be of confidential character, which means that it should not be easily available to the public. In most cases know-how constitutes also a trade secret, protected by the Unfair Competition Act. The second part of the article presents different constructions of the legal protection of know-how, which can be based upon the exclusive right to profit derived from the use and disposal of know-how or upon a generally binding ban on injuring - in an illegal way - the authorized party’s economic interests. The analysis leads to a conclusion, that there is no absolute and exclusive right to profit derived from know-how. The construction of such a right could be well-founded only if the Polish law provided for a regulation authorizing the know-how holder to demand that nobody take advantage of his good. No such a regulation is formulated explicitly in either the Civil Code, the Industrial Property law or in the Unfair Competition Act, therefore it cannot be created by mere interpretation of Law. The legal position of the know-how holder is a factual, not legal exclusivity to profit derived from know-how, based upon its secrecy. It is indirectly protected by law of torts placed in the Civil Code and as a trade secret - by the Unfair Competition Act. Infringing upon the exclusivity through revealing or applying confidential information without the permission of the know-how holder can be considered a tort, when it is done in an illicit way and may cause an obligation to compensate the damages.